Development of a switchable solvent liquid phase extraction method for the determination of chlorthiamid, ethyl parathion, penconazole and fludioxonil pesticides in well, tap and lake water samples by gas chromatography mass spectrometry - Bulgurcuoglu, Ayse Evrim; Durak, Busra Yilmaz; Chormey, Dotse Selali; Bakirdere, Sezgin (ELSEVIER, 2021)
This study presents a switchable solvent liquid phase extraction (SS-LPE) method for the enrichment of four pesticides, and their subsequent determination by gas chromatography mass spectrometry (GC-MS). BoxBehnken experimental design was utilized to attain optimum conditions of the SS-LPE method by navigating a design model developed according to parameter effects and their interactions. Significant parameters were evaluated using analysis of variance (ANOVA), and the optimum variables were selected from a list of combinations presented by the model predictor. The detection limits calculated for chlorthiamid, ethyl parathion, penconazole and fludioxonil were 0.58, 0.73, 0.33 and 0.28 ng/mL. These detection limits correlated to enhancement factors in the range of 60-150 folds. Repeatability based on intra-day and inter-day analysis produced percent relative standard deviations below 10%, a good indicator of high precision. Well water, tap water and lake water samples were employed as real sample matrices to test the trueness of the method and its applicability. The recovery results calculated for the samples spiked at different concentrations were satisfactory (90-105%), and this validated the method for real sample applications.
Keywords: Pesticides; Switchable solvent liquid phase extraction; Box-Behnken design; Gas chromatography mass spectrometry; Green profile; MICROEXTRACTION; FUNGICIDE; RESIDUES; EXPOSURE; Chemistry